(E)‐Ethyl 3‐(3, 4‐dihydroxyphenyl)prop‐2‐enoate: a natural polymorph extracted from Aristotelia chilensis (Maqui). (12th June 2013) - Paz, Cristian; Moreno, Yanko; Becerra, José; Silva, Mario; Burgos, Viviana; Freire, Eleonora; Baggio, Ricardo
Abstract : The natural title compound, C11 H12 O4, extracted from the Chilean native tree Aristotelia chilensis (Maqui), is a polymorph of the synthetic E form reported by Xia, Hu & Rao [ Acta Cryst. (2004), E60, o913–o914]. Both rotational conformers are identical from a metrical point of view, and only differ in the orientation of the 3, 4‐dihydroxyphenyl ring with respect to the rest of the molecule, which leads to completely different crystal structure arrangements and packing efficiencies. The reasons behind both reside in the different hydrogen‐bonding interactions.